Fraud Tendency in Islamic Banks - Mediawati, Elis; Fadhila, Vira Nurul (Universitas Pendidikan Indonesia, 2021)
This study aims to determine the effect of competence and religiosity on the tendency of Â fraud. The research method used in this research is a quantitative research using survey methods. Data collection techniques in this study using a questionnaire. Hypothesis testing in this study uses multiple linear regression analysis, t-test, and F test with the help of SPSS Statistics 20 software. This study indicates that competence has a positive effect on fraud, and religiosity has a negative effect on the trend of fraud. Based on the research results, it is recommended for further researchers to examine the actual process in Islamic banking by looking at aspects of religiosity and organizational culture.